2004
DOI: 10.1002/sia.1701
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic instabilities in the NO/H2 reaction on platinum

Abstract: We have studied the catalytic reduction of nitric oxide (NO) with hydrogen (H 2 ) on platinum using both field ion microscopy (FIM) and pulsed field desorption mass spectrometry (PFDMS). Under certain conditions of temperature and gas pressure this reaction exhibits non-linear behaviour, i.e. hysteresis effects and rate oscillations occur. Ensembles of kink sites of the <100> zones are found to act as pacemakers, which is in line with earlier studies demonstrating f012g planes to ignite in a quasi-concerted ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Indeed, the present atom-probe results have revealed small amounts of (NO) 2 + supporting the above assumption. Similar observations were previously made for Au tips as well [40]. Such dimer species may originate from a gem-dicarbonyl precursor state which for sterical reasons should be preferentially bound to steps/kinks.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, the present atom-probe results have revealed small amounts of (NO) 2 + supporting the above assumption. Similar observations were previously made for Au tips as well [40]. Such dimer species may originate from a gem-dicarbonyl precursor state which for sterical reasons should be preferentially bound to steps/kinks.…”
Section: Discussionsupporting
confidence: 84%
“…This interpretation is also in good agreement with TPD measurements on various Pd single crystal surfaces [19,20]. In contrast to earlier studies with platinum tips [21], the dissociative adsorption of NO on Pd seems to occur on the whole visible surface area without significant preference towards particular facets. Increasing the H 2 :NO ratio to 3.6 is found to cause immediate changes in the total brightness of the imaged tip apex as can be seen in Fig.…”
Section: Bistability During No+ H 2 Interaction Over Pd Tipssupporting
confidence: 90%
“…Kruse and co-workers [53] studied the adsorption of NO on Au 3D hemispherical crystals (''field emitter tips'') by means of pulsed field desorption mass spectrometry (PFDMS) under dynamic gas flow conditions and at 300 K. Mullins's group also showed that the NO uptake on the Au(111) surface is enhanced by the presence of oxygen adatoms, likely due to electronic or structural Hussain et al [50] used DFT to study NO adsorption on Au(111), (100), (110) and (310) surfaces, as well as on adatoms on Au(100). The results clearly show that the adsorption energy of the molecules increases considerably with increasing the degree of coordinative unsaturation of the gold atoms to which the molecules bind.…”
Section: Adsorption Of Nitrogen Oxides and Effect Of Preadsorbed Omentioning
confidence: 99%
“…The detection of small amounts of (NO) 2 + , in turn, indicates that the appearance of N 2 O is caused mainly by the formation of (NO) 2 dimers and their dissociation toward N 2 O and O ad , 61 similarly as it was observed earlier for Au tips. 62 An important process that accompanies often the surface reactions is the change of the oxidation state and of the morphology of the sample. Here, FIM allows again a direct in situ observation, whereas a direct comparison of the local behavior of crystallographically differently oriented facets is possible (Figure 9).…”
Section: Surface Chemistrymentioning
confidence: 99%